2006
DOI: 10.1210/jc.2006-0206
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Role of Small Ubiquitin-Like Modifier 4 as a General Autoimmunity Locus in the Japanese Population

Abstract: These results indicate that the SUMO4 is a more common autoimmune disease gene and a supplementary risk factor to type 1 diabetes in conjunction with class II HLA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…Tsurumaru et al 18 reported SUMO4 M55V to be positively associated The subjects included in this study were 673 consequently diagnosed new onset TIDM patients and 535 healthy controls in the age group of 0-35 years, age-and sex-matched. 21,22 Detailed description of study population are described in references.…”
Section: Resultsmentioning
confidence: 97%
“…Tsurumaru et al 18 reported SUMO4 M55V to be positively associated The subjects included in this study were 673 consequently diagnosed new onset TIDM patients and 535 healthy controls in the age group of 0-35 years, age-and sex-matched. 21,22 Detailed description of study population are described in references.…”
Section: Resultsmentioning
confidence: 97%
“…4 This polymorphism has been associated with susceptibility to AITD, type 1 diabetes (T1D) and rheumatoid arthritis in Asian populations. 5,6 However, the association of M55V with Graves' disease (GD) and T1D could not be replicated in Caucasian populations, suggesting heterogeneity in the genetic effect of the SUMO4 locus among diverse ethnic groups. [7][8][9][10] MAP3K7IP2 (also known as TAB2) encodes a different inhibitor of the NF-kB signaling pathway and a SNP (001Msp) has been shown to be associated with AITD.…”
Section: Introductionmentioning
confidence: 99%
“…Fifty-eight studies were identified by electronic and manual searching and 15 were selected for a full-text review based on title and abstract details [3,[6][7][8][9][10][11][12][13][14][23][24][25][26][27]. Seven reports were excluded because they contained family data [23][24][25][26], duplicated data [9], and data not in HWE [7,27], and thus, eight reports met the inclusion criteria [3,6,8,[10][11][12][13][14].…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…Seven reports were excluded because they contained family data [23][24][25][26], duplicated data [9], and data not in HWE [7,27], and thus, eight reports met the inclusion criteria [3,6,8,[10][11][12][13][14]. However, one study had data on three different groups [8], and one study included five different groups [3], and we analyzed these groups independently.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation